Spectral analysis of the Sturm-Liouville operator given on a system of segments - Snizhana Vovchuk (Annals of Mathematics and Physics - Peertechz Publications, 2023)
The spectral analysis of the Sturm-Liouville operator defined on a finite segment is the subject of an extensive literature [1,2]. Sturm-Liouville operators on a finite segment are well studied and have numerous applications [1-6]. The study of such operators already given on the system segments (graphs) was received in the works [7,8]. This work is devoted to the study of operators